Risks for Aspergillus-Related Diseases: occupational exposure and diseases - Sabino, Raquel (2019)
Environments with high levels of fungal particles are found in different occupational settings, and workers at these working places are at increased risk for occupational respiratory diseases. Fungal particles can include viable and non-viable spores or conidia, hyphal fragments, and even submicron fragments derived from the fungal cell wall. Mycotoxins and other volatile organic compounds should also be considered as potential hazards. Exposure to environmental fungi is associated with worsening asthma symptoms, lung function, hospital admissions, and asthma related deaths. Significant pulmonary pathology is associated with Aspergillus-induced allergic and asthmatic lung disease related to occupational exposure. Alergic bronchopulmonary aspergillosis (ABPA), rhinosinusitis, rhinitis, and severe asthma with fungal sensitisation (SAFS) are among the diseases more frequently associated with Aspergillus occupational exposure. Immunocompromised patients are at higher risk and may develop invasive infections. Aspergillus conidia can be found almost everywhere and are easily disseminated in the air. The size of the conidia is species dependent and Aspergillus conidia can colonize the entire respiratory tree. Aspergillus fumigatus is one of the species most frequently associated with respiratory symptoms due to the small size of the conidia and other virulence factors associated to this species. Nevertheless, fungi belonging to Nigri, Flavi, Circumdati and Versicolores sections must be considered in the risk assessment of a specific occupational environment since there are species that produce airborne mycotoxins within these species-complexes. Other issue of concern in specific occupational settings is the exposure to high levels of azole-resistant Aspergillus isolates, which may increase the risk of workers developing infections with difficult clinical management. During this presentation, we will review and discuss the most recent works related to Aspergillus occupational exposure, potential health effects related to that exposure and preventive or corrective measures suggested to avoid Aspergillus exposure in occupational environments.